Women's perceptions of telephone interviews about their experiences with childbirth care in Nigeria: A qualitative study - Nasir Umar; Zelee Hill; Joanna Schellenberg; Özge Tuncalp; Moise Muzigaba; Nuraddeen Umar Sambo; Abdulrahman Shuaibu; Tanya Marchant (Public Library of Science (PLoS), 2023)
Our objective is to investigate women's perceptions of phone interviews about their experiences with facility childbirth care. The study was conducted between October 2020 and January 2021, in Gombe State, Nigeria. Participants were women aged 15-49 years, who delivered in ten study Primary Health Care centres, provided phone numbers, and consented to a follow-up telephone interview about their childbirth experience. The phone interviews took place 14 months after the delivery and consisted of a quantitative survey about women's experiences of facility childbirth followed by a set of structured qualitative questions about their experiences with the phone survey. Three months later 20 women were selected, based on their demographic characteristics, for a further in-depth qualitative phone interview to explore the answers to the structured qualitative questions in more depth. The qualitative interviews were analysed using a thematic approach. We found that most of the women appreciated being called to discuss their childbirth experiences as it made them feel privileged and valued, they were motivated to participate as they viewed the topic as relevant and thought that their interview could lead to improvements in care. They found the interview procedures easy and perceived that the call offered privacy. Poor network connectivity and not owning the phone they were using presented challenges to some women. Women felt more able to re-arrange interview times on the phone compared to a face-to-face interview, they valued the increased autonomy as they were often busy with household chores and could rearrange to a more convenient time. Views about interviewer gender diverged, but most participants preferred a female interviewer. The preferred interview length was a maximum of 30 minutes, though some women said duration was irrelevant if the subject of discussion was important. In conclusion, women had positive views about phone interviews on experiences with facility childbirth care.